PENYULUHAN TENTANG INFORMASI DAN EDUKASI COVID-19 DI LINGKUNGAN I KELURAHAN WEK V KEC. PADANGSIDIMPUAN SELATAN KOTA PADANGSIDIMPUAN - Harahap, Mei Adelina; Rangkuti, Nur Aliyah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Corona virus or COVID-19, the case started with pneumonia or mysterious pneumonia in December 2019. This case is suspected to be related to the Huanan animal market in Wuhan which sells various types of animal meat, including those that are not commonly consumed, for example snakes, bats, and different types of mice. Many cases of this mysterious pneumonia infection are indeed found in these animal markets. The Corona virus or COVID-19 is thought to be carried by bats and other animals that are eaten by humans until transmission occurs. Corona virus is actually no stranger to the world of animal health, but only a few types are capable of infecting humans and causing pneumonia. The purpose of community service is to increase public knowledge and awareness about Covid-19 Information and Education. The form of activities carried out was counseling on Covid-19 Information and Education at LabuhanRasokiBaru Village in 2020. The extension activities carried out were going well by the community, the activity seemed enthusiastic in participating in counseling activities about Covid-19 information and education in LabuhanRasoki Village. This is evidenced by the enthusiasm of the community carrying out activities regularly and orderly as well as listening to counseling about Covid-19 information and education. And handwashing counseling activities, providing information and education on Covid-19, sticking banners and photos together by the activity committee and the community.